PENGARUH KETERSEDIAAN KOLEKSI PERPUSTAKAAN FAKULTAS ILMU SOSIAL DAN POLITIK USU DALAM PEMENUHAN KEBUTUHAN INFORMASI - Priatmana, Aldi; Ritonga, Sakti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
For library development, one of the most important aspects to consider is the collection of information. The purpose of this study focuses on the effect of the availability of online proquest journals on meeting user information needs in the Library of the Faculty of Social and Political Sciences USU. This type of research is descriptive research using qualitative approach methods. This research data collection technique is through observation, interviews, and documentation. The result of this study is the availability of online ProQuest journals in the Library of the Faculty of Social and Political Sciences, based on good perceptions of library users, and the affirmation of library users that they are looking for reference materials for lecture assignments from online ProQuest journals rather than libraries. It has been used effectively by library patrons as a resource to aid in the creation of coursework. This journal provides a source of current and accurate information that can be used as a reference when completing courses and research. Thus, Proquest Journal has a significant impact on users' information demands. Library of the Faculty of Social and Political Sciences, University of North Sumatra.